Depression among diabetes mellitus patients: A study of the protective factors - Putri Nur Azizah; Herlina Siwi Widiana; Siti Urbayatun (International Journal of Public Health Science (IJPHS), 2021)
Diabetes mellitus is a chronic disease with patients that continue to increase per year. This study aimed to understand the role of self-esteem and religious orientation on depression with resilience as a mediator among patients with diabetes mellitus (DM). A total of 100 patients were recruited from four public health centers. The Center for Epidemiologic Studies Depression Scale (CES-D) was used to measure depression. In contrast, self-esteem was measured using two aspects of Rosenberg’s self-esteem scale, namely self-liking and self-competence. Religious orientation was measured using Allport and Ross’s religious orientation scale, while resilience was measured using Connor and Davidson’s resilience scale. The results were analyzed using path analyses. The study found that resilience mediated the relationship between self-esteem and depression among DM patients. Self-esteem was also shown to correlate with resilience, and resilience also showed a significant relationship with depression. In contrast to initial predictions, however, there was no significant effect of religious orientation on resilience. The research implications suggest that resilience serves as an important protective factor toward depression among patients suffering from DM.